2021
DOI: 10.1186/s12947-021-00270-1
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial strain measured via two-dimensional speckle-tracking echocardiography in a family diagnosed with arrhythmogenic left ventricular cardiomyopathy

Abstract: Background Arrhythmogenic cardiomyopathy is a myocardial disorder characterized by ventricular arrhythmias, right and/or left ventricular involvement, and fibrofatty infiltrations in the myocardium. We report a family diagnosed with arrhythmogenic left ventricular cardiomyopathy (ALVC) and depict their echocardiographic characteristics. Methods and results Fifteen family members were divided into three groups based on whether they carried the TMEM4… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Combining both deformation patterns and mechanical dispersion has been shown to improve the sensitivity for identifying subclinical disease and the predictive value for risk stratification. [34][35][36][37][38][39][40][41] Mast et al and Kirkels et al showed that pattern recognition adds prognostic value and helps to predict disease progression. 32,34 Regional patterns such as delayed onset of shortening, reduced peak systolic strain, and mild post-systolic shortening may be observed in early ACM phenotypes, which often present before fulfilment of electrical or structural 2010 TFC.…”
Section: D Longitudinal Strain Imagingmentioning
confidence: 99%
“…Combining both deformation patterns and mechanical dispersion has been shown to improve the sensitivity for identifying subclinical disease and the predictive value for risk stratification. [34][35][36][37][38][39][40][41] Mast et al and Kirkels et al showed that pattern recognition adds prognostic value and helps to predict disease progression. 32,34 Regional patterns such as delayed onset of shortening, reduced peak systolic strain, and mild post-systolic shortening may be observed in early ACM phenotypes, which often present before fulfilment of electrical or structural 2010 TFC.…”
Section: D Longitudinal Strain Imagingmentioning
confidence: 99%
“…Previous studies have confirmed 1,14 that left ventricular global longitudinal strain (LVGLS) can accurately evaluate left ventricular systolic function, while GLS is affected by volume load 15 . Recently, experts recommended 16–18 to add left atrial strain to the evaluation of left ventricular diastolic function.…”
Section: Discussionmentioning
confidence: 99%
“…Conduit function is the difference between reservoir function and contractile function. In the early stage of ventricular diastole, blood flows directly into left ventricle through left atrium, which is mainly determined by left atrial compliance, and is also closely related to left ventricular diastolic tension and stiffness 14 . After hemodialysis, the strain value of LAScd also decreased, indicating that the blood flowing through left atrium and entering left ventricle decreased in early diastole.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Mast et al [61] observed that in relatives of ARVC patients normal sub-tricuspid regional strain is associated with no disease progression in the next 4 years follow-up, strain abnormalities possibly anticipating the overt signs of the disease. To date there are only a few reports describing LV strain abnormalities in the setting of ACM [62]. 3D echocardiography enables a more accurate measurement of RV volumes and ejection fraction, thereby overcoming the geometrical limits of 2D RV imaging, that underestimates RV volumes.…”
Section: Echocardiographymentioning
confidence: 99%